Hospital Performance Assessment Clustering in North Sumatra by using K-Means Algorithm - Lumban Gaol, Adi Putra; Agustina Simangunsong (Login : Jurnal Teknologi Komputer, 2023)
The hospital is an integral part of the entire health care system that serves patients with various types of services. The hospital assessment system is an effort to provide a tool that encourages the hospital to continuously improve the quality and safety of services. Thus the hospital must apply hospital accreditation standards, including other standards that apply to hospitals in accordance with the description in the Hospital Accreditation Standards. Data mining is a process of finding meaningful relationships, patterns, and trends by examining a large set of data stored in storage using pattern recognition techniques such as statistical and mathematical techniques.In this research the data mining algorithm used is the K-Means Clustering Algorithm. The simplest and most common method is because K-Means has the ability to classify large amounts of data in a relatively fast and efficient computation time.